Clinical and molecular characterization of familial chylomicronemia in Saudi patients: a retrospective study - Al-Ashwal, Abdullah; AlHelal, Manal; AlSagheir, Afaf; Alfattani, Areej; Ramzan, Khushnooda; Imtiaz, Faiqa; Alhuthil, Raghad (Frontiers in Endocrinology, 2024)
Familial chylomicronemia syndrome (FCS) is a severe type of hypertriglyceridemia(HTG). It is a rare autosomal recessive disorder caused by a genetic defect in intravascular lipolysis. It requires urgent and proper management because serious cases can be accompanied by pancreatic necrosis, persistent multiple organ failure, and higher mortality rates. The rarity of FCS makes it more challenging for scientists and clinicians to achieve advancements in its management. Despite its rarity, we have encountered more than 100 patients with FCS at our center (King Faisal Specialist Hospital and Research Centre [KFSH&RC], Riyadh, Saudi Arabia). In this retrospective study, we analyzed the data of 29 patients with FCS and described the clinical, biochemical, and molecular characteristics and management of this cohort. We aimed to provide a useful resource for clinicians who may encounter such patients and help the scientific community accumulate knowledge to efficiently manage this disease.